The Analysis of Gender Inequality in Two Dramas - Pratiwi, Ricka Galuh (Journal of Literature, Linguistics, & Cultural Studies, 2023)
Gender inequality is the term used to describe how men and women are treated differently. The target individual or group typically suffers or is disadvantaged as a result of inequality. This study's goal is to describe several types of gender inequality as they appear in Mansour Fakih's theory. Aside from that, consider how female characters approach gender inequity. Using data from the dramas A Raisin in the Sun by Lorraine Hansberry and Heart in the Ground by Doughlas Hill, this study adopts a feminist methodology and Mansour Fakih's concept of gender inequality. Literary criticism is the technique employed. Then, information is gathered by reading and documenting information that is pertinent to the theory and research issues. The results obtained from this study are (1) The two dramas each have three types of gender inequality. In Heart in The Ground there are subordination, violence and double burden. Three different types of women's inequality such as subordination, stereotypes, and marginalization are present in Hansberry's second play, A Raisin in the Sun. (2) Four ways to achieve their rights: rebelling, threatening, and talking about it, focusing on their goal.Keywords: Feminism, Gender Inequality, Drama